PENGARUH EKSTRAK DAUN KERSEN (Muntingia calabura) DENGAN DOSIS BERBEDA TERHADAP LAMA INKUBASI, DAYA TETAS DAN KELULUSHIDUPAN LARVA IKAN LELE DUMBO (Clarias gariepinus) - Harni Sri Mulyani; T. Iskandar Johan (UIR Press, 2020)
ABSTRACT This study aims to determine the effect of the optimal dose of cherry leaf extract solution on incubation time, hatchability, and survival of larvae of catfish (Clarias gariepinus). The research used an experimental method using a Completely Randomized Design (CRD) with 5 treatments and 3 replications, namely: (P1) 2,0 gr/l, (P2) 2,5 gr/l, (P3) 3,0 gr/l , (P4) 3,5 gr/l and (P5) 4,0 gr/l. The test eggs used came from artificial spawning at the Fish Seed Center (BBI), Riau Islamic University. The container used is a jar with a capacity of 10 liters of 15 pieces. This research was conducted for 21 days on October 2019 at the Laboratory of Fish Seed Center (BBI), Faculty of Agriculture, Riau Islamic University, Pekanbaru. The results showed that the best adhesion was found on (P5) 4,0 gr/l of 98,89%. The incubation time and hatchability of the best treatment at (P3) 3,0 gr / l, the incubation time is 17 hours 27 minutes with a hatchability of 83,33%. Furthermore, the best treatment life was on (P2) 2,5 gr/l was 42,08%. The results of measurements of water quality parameters in this study had temperatures ranging from 290 C - 340 C, pH 6,0-6,5, ammonia between 0,28-0,97 and DO range between 3,14-3,81. Keywords: Dumbo catfish, Long incubation, Hair power, Graduation, Cherry leaves, Hatchability